ANALISIS FENOMENOLOGI BANK MENDIRIKAN KOPERASI KREDIT - Dwiyoso, Hertoto; Susanto, M. Harri; Kaluge, David (Journal of Indonesian Applied Economics, 2008)
The approach used in this research is phenomenology as the object of the researchis a reality hidden in human awareness.  The analysis process of findings in thisresearch is based on interactive model of analysis by Miles and Huberman, andsome idea from Husserl, Weber, Schutz and Berger.  Moreover, it is necessary toappreciating  this  reality  with  a  fully  comprehension  (verstehen)  because  thetrue reality hidden in human awareness. Some significant findings are found inthis research.   First,  the reality  that  the bank  establishing credit cooperationappears  in phases of interaction and deeply  thought, and also as reflection ofother interconnected realities. Second, the goal in establishing credit cooperationis for the sake of satisfying the desire for getting profit as many as possible.  Thecooperation is used as a mask covering the real fact that it  is only a mean  foravoiding  the  regulation.   Third,  the  act  of  establishing  credit  cooperation  isactually an effort  to  legalize  the practice of bank  inside bank as  the practiceinvolved is the same, but now it has legally cooperation practice.Keywords: agency problem, the practice of bank inside bank, credit cooperation.